A nonproteinaceous Fusarium cell wall extract triggers receptor‐like protein‐dependent immune responses in Arabidopsis and cotton. Issue 1 (9th January 2021) - Babilonia, Kevin; Wang, Ping; Liu, Zunyong; Jamieson, Pierce; Mormile, Brendan; Rodrigues, Olivier; Zhang, Lin; Lin, Wenwei; Danmaigona Clement, Catherine; Menezes de Moura, Stéfanie; Alves‐Ferreira, Marcio; Finlayson, Scott A.; et al.
Summary: Fusarium wilt caused by the ascomycete fungus Fusarium oxysporum is a devastating disease of many economically important crops. The mechanisms underlying plant responses to F. oxysporum infections remain largely unknown. We demonstrate here that a water‐soluble, heat‐resistant and nonproteinaceous F. oxysporum cell wall extract (FoCWE) component from multiple F. oxysporum isolates functions as a race‐nonspecific elicitor, also termed pathogen‐associated molecular pattern (PAMP). FoCWE triggers several demonstrated immune responses, including mitogen‐activated protein (MAP) kinase phosphorylation, reactive oxygen species (ROS) burst, ethylene production, and stomatal closure, in cotton and Arabidopsis. Pretreated FoCWE protects cotton seeds against infections by virulent F. oxysporum f. sp. vasinfectum ( Fov ), and Arabidopsis plants against the virulent bacterium, Pseudomonas syringae, suggesting the potential application of FoCWEs in crop protection. Host‐mediated responses to FoCWE do not appear to require LYKs/CERK1, BAK1 or SOBIR1, which are commonly involved in PAMP perception and/or signalling. However, FoCWE responses and Fusarium resistance in cotton partially require two receptor‐like proteins, GhRLP20 and GhRLP31. Transcriptome analysis suggests that FoCWE preferentially activates cell wall‐mediated defence, and Fov has evolved virulence mechanisms to suppress FoCWE‐induced defence. These findings suggest that FoCWE is a classical PAMP that is potentially recognised by a novel pattern‐recognition receptor to regulate cotton resistance to Fusarium infections.